Spread Spectrum Process Using Direct Sequence Spread Spectrum (DSSS) and Frequency Hopping Spread Spectrum (FHSS) - N. A., Handrizal; Noraziah, Ahmad; Abdalla, Ahmed N. (2009)
This paper presents spread spectrum process using Direct Sequence Spread Spectrum (DSSS) and Frequency Hopping Spread Spectrum (FHSS). DSSS is type spread spectrum the most widely known and most widely used. Mean while, in FHSS the data is modulated directly onto a single carrier frequency, but that carrier frequency hops across a number of channels within the RF band using a pseudo-random hopping pattern. We compare between DSSS and FHSS in terms of channel, narrowband interference, main parameters, co-location, security and cost. DSSS performance better in terms of cost and this system is recognized most easily implementation, while FHSS superior in narrowband interference, co-location channel and security.